Göçmenlere Yönelik Ayrımcılık ve Ayrımcılık Karşıtı Sosyal Hizmet Uygulamaları - Köksal, Sevde (Göç ve Sosyal Hizmet, 2023)
While global migration movements have affected many changes in the social structure, they have also brought discrimination. It is seen that the negative impact of migration between the local people and the immigrant group has brought many conflicts from the historical process to the present day by creating a perception of threat to the outgroup. In the face of xenophobia brought about by migration and migration, the practices of the social work discipline on the basis of human rights regarding the fight against discrimination manifest themselves. Anti-discrimination practice, which manifests itself in this sense and combines its practice with other approaches, exhibits its roles such as advocacy, education, counseling and public opinion formation. The discipline of social work moves the exclusion experienced by migrant communities from the micro dimension to the macro dimension of mobilizing social resources with national and international legal bases against discrimination. At the same time, it has the role of revealing the framework of the dynamics of discrimination by revealing its causes, consequences, risks and intersectional effects within the framework of the knowledge obtained from other social sciences. It is possible to say that xenophobia and discrimination are perpetuated between the local people and the migrant group, especially due to the lack of intergroup contact. In this sense, practices related to increasing contact and interaction were evaluated as approaches that would benefit the groups to get to know each other in real terms. In social life, discrimination and discrimination-related oppression and exclusion phenomena are produced by social structures, and it is important that anti-discrimination practices are shaped within the framework of transforming these structures. In this sense, it is possible to consider xenophobia, which has the potential to increase in parallel with discrimination and globalization, as a social risk that manifests itself at the global level. It is evident that more needs to be done for the whole world regarding the adequacy and inclusiveness of existing anti-discrimination policies and practices regarding the capacity of this risk to affect all social systems.